2021
DOI: 10.1061/(asce)he.1943-5584.0002070
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Climate Variability and Drought Characteristics in Tropical Region of India

Abstract: This work reports climate change signals and long-term trend analysis of climate variables, meteorological drought, and extreme climate indices over the tropical state of Kerala in India. The trend analysis reveals statistically significant decrease of annual and southwest monsoon rainfall (as much as 63 mm and 55 mm per decade respectively). A decrease in number of annual rainy days (up to 2.8 days/decade) is also reported. Temperature trend analysis indicates an increasing 2 trend with as high as 1.3°C/decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…On the other hand, RCP 8.5 portrayed an increasing trend of mean temperature in both the catchments ranging between 4.69 to 14.11% for Aghanashini and 4.69 to 14.45% for the Gurupura river catchment. The increase in mean temperature for RCP 8.5 could be attributed to warming patterns globally and have been reported in several watersheds of the Western Ghats of India (Mudbhatkal et al, 2017;Mudbhatkal & Amai, 2018b;Sharannya et al, 2018;Sinha & Eldho, 2018;Vijay et al, 2021).…”
Section: Climate Scenariomentioning
confidence: 66%
“…On the other hand, RCP 8.5 portrayed an increasing trend of mean temperature in both the catchments ranging between 4.69 to 14.11% for Aghanashini and 4.69 to 14.45% for the Gurupura river catchment. The increase in mean temperature for RCP 8.5 could be attributed to warming patterns globally and have been reported in several watersheds of the Western Ghats of India (Mudbhatkal et al, 2017;Mudbhatkal & Amai, 2018b;Sharannya et al, 2018;Sinha & Eldho, 2018;Vijay et al, 2021).…”
Section: Climate Scenariomentioning
confidence: 66%
“…The maximum and minimum annual mean temperature over the region is 32.70°C, 21.20°C approximately. The highest annual rainfall in the Central part (Karnataka) of the WG than other parts and decreases in the intensity towards the north of the Ghat (Shetty et al, 2022; Vijay et al, 2021) are intently captured in all the ensemble models. The apprehension of the heterogeneity in the distribution of temperature and rainfall by the RFR, XGBR and ETR ensemble of CMIP6 directs the use of GCMs even in the river basin scale.…”
Section: Resultsmentioning
confidence: 98%
“…The rest of the seasons and annual rainfall did not show any significant trend over the years. A study by Vijay et al [62] revealed a declining trend of annual and seasonal rainfall for the entire state of Kerala over 118 years ending in 2018. Adarsh and Janga Reddy [63] indicated that the annual rainfall in the Kerala meteorological sub-division shows a significant decreasing trend, along with a similar decreasing trend in Jun rainfall as well.…”
Section: Rainfall Trend and Distribution Over Keralamentioning
confidence: 99%